KINETIKA PENURUNAN ASAM LEMAK TIDAK JENUH GANDA PADA OLAHAN TELUR DAN IKAN - Komari, Komari (Universitas Djuanda Bogor, 2010)
Long chain omega-3 fatty acids such as Eicosapentaenoic acid (EPA) and Docosahexaenoic (DHA), were very important for brain development, immunity, retina and growth of child. One of natural source of these faty acids is fish which has been processed into variety food such as abon. The other source is modifying hen egg which potentially to be added into many kind of food after processed as egg flour. This research examine the effect of processing and storage of abon and eggs flour. The methode of this research was one-group pre post test (minimal control) and the date was prepared in tabulation. Processing in to abon ikan make EPA lost for 10,63% and DHA 7,63%. This product was acceptable, but the stability of the fatty acids were low, EPA lost 43,8% and DHA lost by 52,4% for 4 months. The eggs prepared by our lab contained 2,5% omega-3 fatty acid. To make egg yolk flour was used Spray Drying process. This process make EPA lost 43,94% and DHA 6,20%. After storing for 4 months, egg yolk flour was very stabile. Because of these reason, these products can be used to supplement fatty acids in daily diet. Eggs flour can be used in any food product to supply omega-3 fatty acid for the risk group.